A pilot study of commonly held misconceptions in secondary school genetics - Moore, Aldyth Margaret (Rhodes University, Faculty of Education, Department of Education, 1990)
This pilot study was aimed at investigating with the aid of a two-tier multiple choice questionnaire, the misconceptions held by pupils in standards 8 and 10 as well as first year Biology students in the area of senior secondary school genetics. It was found that certain of the children's preconceived ideas were altered by tuition while others were unaffected by either age or tuition and consequently warranted the name misconceptions. Four misconceptions were identified in this study and these were seen to be at the root of the difficulties experienced in genetics. They involved plants being seen to be unable to reproduce sexually, an inability to relate meiosis to genetics, a tendency to cling to the Punnett square algorithm when solving genetics problems despite a lack of understanding of the underlying processes and a failure to see the role of chance in genetics. These misconceptions were seen to have arisen because of certain preconceived ideas which hamper the formation of a suitable conceptual framework. The adoption of suitable teaching strategies appears to be the most likely method of rectifying the problem. However, before this can be regarded as conclusive, further research into the concept development of specific aspects such as sexual reproduction, needs to be done. Studies to investigate the most suitable teaching strategy should also be carried out as well as an investigation into the structure of the curriculum
Keywords: Genetics -- Study and teaching (Secondary)